Purification of Neurospora myo-inositol-l-phosphate synthase by affinity chromatography - J. Aradi; A. Zsindely; A. Kiss; M. Schablik (Fungal Genetics Reports, 1980)
Purification of Neurospora myo-inositol-l-phosphate synthase by affinity chromatography.